Comorbidity of the Metabolic Syndrome: Hyperuricemia, Gallstone Disease, Hormonal Disorders - Raisa A. Aringazina (Journal of Global Pharma Technology, 2019)
This article presents relationships between metabolic syndrome and gallstone disease, hyperuricemia, hormonal disorders and point out the most relevant picture for today. In the review the general pathogenetic mechanism of endothelial dysfunction formation in metabolic syndrome and hyperuricemia is revealed and described. Shown, that hyperuricemia is a marker of the metabolic syndrome. The symptoms of metabolic syndrome increase with increasing levels of hyperuricemia. The review found that it is obesity and insulin resistance are common leading risk factors for progression metabolic syndrome and gallstone disease. No association between gallstone disease and dyslipidemia unlike metabolic syndrome. Obesity is a common factor in the relationship between metabolic syndrome, gallstone disease and hormonal disorders. Insulin resistance is a common factor metabolic syndrome and polycystic ovary syndrome, the leading factor in the course of metabolic syndrome in menopause, hypopituitarism, and gallstone disease. Also, insulin resistance is a common factor in the comorbidity of gallstone disease and postmenopausal conditions. Obesity and insulin resistance are common factors of metabolic syndrome and benign prostate hyperplasia. Keywords: Metabolic syndrome, Uric acid, Gallstone disease, Hyperuricemia, Hormonal disorders.